Tubuh yang Mencipta Momen: Praktik Negosiasi Tubuh dalam Tari Wajah Karya Hartati - Roza Muliati; Wening Udasmoro; Sal Murgiyanto (Jurnal Kajian Seni, 2019)
The practice of the body in contemporary dance is always marked by novelty and invention. For Indonesian choreographers, contemporary dance is a practice of negotiation that brings the influence of tradition from the past into contemporary body. This paper is intended to reveal the practice of body negotiation in Wajah (2013), a dance work of Hartati, an Indonesian choreographer of Minangkabau descent who is known for her progressive dance works. It is one of Hartati’s dance work which reflect her background as a choreographer embodied two different traditions, namely the Minangkabau tradition and the urban Jakarta. The non-linear experience of the body became the foundation of Hartati’s creativity in the creation of his contemporary works. Therefore, Wajah is an experimental dance, a result of negotiation which bring together the influence of Minangkabau dance tradition based on silat with another influences like balet and daily movements into contemporary bodies. By applying the perspective of embodiment, this paper analysed the performative text as well as the negotiation practice in the making process of dance. This practice has resulted an extra daily technique with moment making orientation.